Building Educational Resilience through Education 4.0 in Africa - Gougou, Saman Ange-Michel; Palé, Hoho Inès (International Journal of Qualitative Research, 2025)
This paper aims to describe the digitalization in Educative system in Côte d’Ivoire according to the Education 4.0 paradigm to promote digital appropriation and build social resilience in a challenging context. Through a multisite ethnography case study in Côte d’Ivoire, a West African country, observation, interviews, and focus groups were used to collect data from a convenience sample of 20 participants (students, educators, parents, administrators) settled in 3 cities of the country. Based on Education 4.0 lenses, findings underlined the benefits and challenges of techno-pedagogy and technology integration according to Educative institutions' capacities in terms of Competencies, Learning methods, Information and communication technologies (ICT) categories, and Infrastructure levels. Moreover, participants show the integration of 21st century learning as an approach to support digital as a tool of educative resilience. As recommendations, an educative system approach including techno-pedagogy and 21st century pedagogy is a strategic approach for an effective educative system in Côte d’ Ivoire in this changing world, according to SDGs and internationalization of education trends.